8th RILEM International Symposium on Testing and Characterization of Sustainable and Innovative Bituminous Materials - Canestrari, Francesco; Partl, Manfred N.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2016)
This work presents the results of RILEM TC 237-SIB (Testing and characterization of sustainable innovative bituminous materials and systems). The papers have been selected for publication after a rigorous peer review process and will be an invaluable source to outline and clarify the main directions of present and future research and standardization for bituminous materials and pavements. The following topics are covered: - Characterization of binder-aggregate interaction - Innovative testing of bituminous binders, additives and modifiers - Durability and aging of asphalt pavements - Mixture design and compaction analysis - Environmentally sustainable materials and technologies - Advances in laboratory characterization of bituminous materials - Modeling of road materials and pavement performance prediction - Field measurement and in-situ characterization - Innovative materials for reinforcement and interlayer systems - Cracking and damage characterization of asphalt pavements - Recycling and re-use in road pavements This is the proceedings of the RILEM SIB2015 Symposium (Ancona, Italy, October 7-9, 2015). .
Romeo, V. Ghizzardi, S. Rastelli, A. Montepara -- Energy Dissipation in Asphalt Mixtures Observed in Different Cyclic Stress-Controlled Fatigue Tests, by I. Isailović, A. C. Falchetto, M. P. Wistuba -- Deterioration of HMA Partially Saturated with Water or Brine Subjected to Freeze-Thaw Cycles, by S. Lamothe, D. Perraton, H. Di Benedetto -- Experimental study of moisture sensitivity of aggregate-bitumen bonding strength using a new pull-off test, by J. Zhang, A. K. Apeagyei, J. Grenfell, G. D. Airey -- Effect of Fine Aggregate Composition on Moisture Susceptibility of Hot Mix Asphalt, by G. LM Leung, A. W. G. Wong -- Evaluation of rutting properties of bituminous binders by means of single shear creep-recovery (SSCR) tests and correlation with mixture performance, by E. Santagata, O. Baglieri, M. Alam, P. Riviera -- Mechanisms of Failure in Uniaxial Repeated Creep Test and the Relationship to Aggregate Packing, by N. Roohi Sefidmazgi, H. U. Bahia -- Development of a test and classification method to objectively determine the colour of coloured bituminous pavements, by K. Denolf, N. Piérard, A. Vanelstraete -- A new performance test for resistance to ravelling by traffic: laboratory and field experience in Belgium, by J. De Visscher, A. Vanelstraete -- Part IX. Field measurement and in-situ characterization -- Active Filler's Effect on in-situ Performances of Bitumen Emulsion Recycled Mixtures, by G. Betti, G. Airey, K. Jenkins, A. Marradi, G. Tebaldi -- Innovative longi.
Keywords: Building materials; Mechanics, Applied; Building Materials; Structural Materials; Engineering Mechanics